The cytotoxic activities of the ethyl acetate and butanol crude extracts of marine cyanobacteria collected from Udar Island, Malaysia - Annisa Krisridwany; Tatsufumi Okino (Universitas Ahmad Dahlan, 2020)
The ocean is abundant in organisms beneficial to living beings, including cyanobacteria that are widely studied for their bioactive compounds. This research was conducted to observe the compounds and concomitant cytotoxic activities of cyanobacteria in Udar Island waters, Sabah, Malaysia, against cancer cells. The samples were identified by the 16S DNA method, and a phylogenetic tree was built to check similarities in the genus. The samples were extracted using ethyl acetate and butanol. Afterward, the compounds were determined by Liquid Chromatography-Mass Spectrometry (LCMS), while the cytotoxicity activities were examined by the MTT assay. Several known compounds in ethyl acetate crude extract, such as several types of Apratoxins, and possible new compounds were observed. The compounds examined were mainly peptide. The crude ethyl acetate extracts of Moorea sp. in Udar Island waters were found to contain cytotoxic compounds, with the IC50 value of 0.072 Âµg/mL against the MCF-7 breast cancer cell lines, that were more potent compared to the butanol crude extract, whose IC50 was 2.031 Âµg/mL. Further isolation and cytotoxic tests are necessary to confirm which compounds are responsible as cytotoxic agents. This finding provides an opportunity for the discovery of anticancer compounds from marine cyanobacteria.